If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.08 + -0.01(x + 2) = -0.02(3 + -1x) Reorder the terms: 0.08 + -0.01(2 + x) = -0.02(3 + -1x) 0.08 + (2 * -0.01 + x * -0.01) = -0.02(3 + -1x) 0.08 + (-0.02 + -0.01x) = -0.02(3 + -1x) Combine like terms: 0.08 + -0.02 = 0.06 0.06 + -0.01x = -0.02(3 + -1x) 0.06 + -0.01x = (3 * -0.02 + -1x * -0.02) 0.06 + -0.01x = (-0.06 + 0.02x) Solving 0.06 + -0.01x = -0.06 + 0.02x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.02x' to each side of the equation. 0.06 + -0.01x + -0.02x = -0.06 + 0.02x + -0.02x Combine like terms: -0.01x + -0.02x = -0.03x 0.06 + -0.03x = -0.06 + 0.02x + -0.02x Combine like terms: 0.02x + -0.02x = 0.00 0.06 + -0.03x = -0.06 + 0.00 0.06 + -0.03x = -0.06 Add '-0.06' to each side of the equation. 0.06 + -0.06 + -0.03x = -0.06 + -0.06 Combine like terms: 0.06 + -0.06 = 0.00 0.00 + -0.03x = -0.06 + -0.06 -0.03x = -0.06 + -0.06 Combine like terms: -0.06 + -0.06 = -0.12 -0.03x = -0.12 Divide each side by '-0.03'. x = 4 Simplifying x = 4
| 99=.5h+11 | | 6(y-1)/5=-2y | | 5x-2=5(x-4) | | 10x^2+3x+m=0 | | -3+6=x-10 | | x+x+x+3x=48 | | x^2+y^2=80 | | 3/7x+4/7=-8/7 | | x+x+x+6x=27 | | 2.5y+4=2y-1 | | 9(y+10)+y=2(y+3)-5 | | .4x+.8= | | -7z+3z=8z-3-z | | 2-8/2(x-1)^2+15 | | .75y-7=-1 | | 31/3/55/12 | | 4x-9=5x-4 | | 3-3/2=7*3/2-9 | | (6x^3-5x^2-4x+3)/(x-1) | | (5-y)(2y-7)=0 | | 2*15/4-6+15/4=6*15/4+9 | | 8(y+2)+y=2(y+2)+7 | | 23x-16=205 | | .67x=14 | | .75y-.5=7 | | (6x^3-5x^2-4x+3)/x-1 | | 9-2x-5-4x=7 | | 2(4x+3)=8x+6 | | 8y-1=4y+9 | | 0.25x+27=41 | | -0.572x=-8 | | -4(n+5)=8-3n |